Comparison of the germination rates of Metarhizium spp. conidia from Japan at high and low temperatures - Nishi, O.; Iiyama, K.; Yasunaga‐Aoki, C.; Shimizu, S. (Letters in applied microbiology, 2013)
The knowledge of the growth characteristics of entomopathogenic fungi at different temperatures is very important for understanding their ecology and field efficacy as biological control agents. However, the relationships between their DNA‐based phylogenetic tree classifications and growth characteristics at different temperatures have not been adequately investigated. In this study, we compared the phylogenetic relationships between Metarhizium anisopliae sensu lato and M. flavoviride isolates obtained from soils in various environments in Japan and the germination rates of their conidia on agar medium in hot and cold conditions. The results showed that the 89 Japanese isolates belonged to the clade of eight species, according to the molecular phylogenetic analysis. The germination rates of isolates belonging to the M. brunneum and M. flavoviride var. pemphigi clades were higher at lower temperatures (9·7–11·0°C) and lower at higher temperatures (34·3–35·2°C) compared with the other six species. The isolates of these two species originated from different geographical regions in Japan, despite their uniform germination characteristics. This study detected the clear interspecific differences in the in vitro germination characteristics of the Japanese isolates of Metarhizium spp. at two different temperature regimes. Significance and Impact of the Study The relationships between the growth characteristics and phylogenetic placements have not been adequately investigated in species of the entomopathogenic fungus Metarhizium. This study determined the relationships between the germination rates in hot and cold conditions and the phylogenetic placements of 89 Japanese soil isolates of Metarhizium spp. Fourteen isolates each of M. brunneum and M. flavoviride var. pemphigi, identified by molecular phylogenetic analysis, showed relatively high germination rates at lower temperatures and low germination rates at higher temperatures compared with isolates, which were identified as six other species. This study detected a strong relationship between the phylogenetic placements of Japanese Metarhizium spp. isolates and their in vitro germination characteristics. Significance and Impact of the Study: The relationships between the growth characteristics and phylogenetic placements have not been adequately investigated in species of the entomopathogenic fungus Metarhizium. This study determined the relationships between the germination rates in hot and cold conditions and the phylogenetic placements of 89 Japanese soil isolates of Metarhizium spp. Fourteen isolates each of M. brunneum and M. flavoviride var. pemphigi, identified by molecular phylogenetic analysis, showed relatively high germination rates at lower temperatures and low germination rates at higher temperatures compared with isolates, which were identified as six other species. This study detected a strong relationship between the phylogenetic placements of Japanese Metarhizium spp. isolates and their in vitro germination characteristics.